Effect of insurance type on stage at presentation, surgical approach, tumor recurrence and cancer-specific survival in resectable non-small lung cancer patients - Sophon Siwachat (2020)
© 2020 Siwachat et al. Purpose: The aim of this study was to identify the association between Thailand’s insurance types and stage at presentation, surgical approach, tumor recurrence and can-cer-specific survival in resectable non-small cell lung cancer (NSCLC) patients in northern Thailand. Patients and Methods: Medical records of patients with NSCLC who underwent pulmonary resection at Chiang Mai University Hospital from January 2007 through December 2015 were retrospectively reviewed. Patients were divided into two groups: patients with the Universal Coverage Scheme (UCS) or Social Security Scheme (SSS) and patients with the Civil Servant Medical Benefit Scheme (CSMBS) or private insurance (PI). Patient characteristics were assessed. The primary outcome was cancer-specific survival while the secondary outcome was tumor recurrence. Cox’s regression and matching propensity score analysis was used to analyze data. Results: This study included 583 patients: 344 with UCS or SSS and 239 with CSMBS or PI. Patients with UCS or SSS were more likely to be active smokers, have a lower percent predicted FEV1, present with higher-stage tumors and worse differentiated tumors, present with tumor necrosis, and undergo an open surgical approach than those with CSMBS or PI. At multivariable analysis of all patients cohort, there were no significant differences in terms of early stage at presentation (adjusted odds ratio (ORadj) = 0.94, 95% confidence interval (CI) = 0.65–1.37), undergoing lobectomy (ORadj = 0.59, 95% CI = 0.24–1.46), and recurrent-free survival (adjusted hazard ratio (HRadj) =1.20, 95% CI = 0.88–1.65) between groups (UCS/SSS versus CSMBS/PI). However, patients with UCS or SSS had shorter cancer-specific survival (HRadj = 1.61, 95% CI = 1.22–2.15). The results from the propensity score matched patient cohort were not different from those analyses on the full patient cohort. Conclusion: Thai insurance types have an effect on cancer-specific survival. The Thai government should recognize the importance of these differences, and further multi-center studies with a larger sample size are warranted to confirm this result.